Comparison of CT number between conventional CBCT and imasim software - Ahamad, Nor Fadhilah (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2015)
The aim of this study was to compare the CT number between the conventional Cone Beam Computed Tomography (CBCT) and ImaSim simulation software. The CT numbers in CBCT were performed by using CIRS 062 M electron density phantoms with four types of tissue equivalent plug density phantoms ranging from 0 g/cm3 to 1.61 g/cm3 based on the common tissues in the oral cavity. The CT numbers of tissue equivalent density plugs were of air, adipose, water and bone were compared between CBCT and ImaSim software at 80 kVp and 10 mAs. 15 slices of CBCT images with slice thickness of approximately 1.0 mm are obtained from central axis of phantom were selected to measure the average CT number by drawing a region of interest (ROI) on every slice. The images of ImaSim were obtained by simulation of CBCT at similar phantom set up and CBCT exposure factors. The measurement of chi-square 'goodness of fit' was used to determine the closeness of CT numbers among theoretical, Planmeca Romexis CBCT and ImaSim. The results showed that the x2 values of CT numbers of theoretical value against Planmeca Romexis CBCT were between 0.651 and 5.206 while the x2 values of theoretical value against lmasim CBCT was between 3.738 and 42.201. However, the range of x2 for Planmeca Romexis CBCT vs lmaSim CBCT was between 1.877 and 58.887. In conclusion, the high density tissues such as bone gave the highest degree of closeness of CT numbers between Planmeca Romexis CBCT and lmaSim. Therefore, low density tissues are best applied in ImaSim CBCT simulation.